Analysis of Ancient Literary Excerpts (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This scientific article studies the specific aspects of the history of philological analysis from the perspective of linguistic poetics. The study attempts to demonstrate the decisive role of “Dīwān Lughāt al-Turk” in the study of linguistic poetics based on evidence. In addition, the article highlights the aspects of the work that are particularly important for linguistics and literary studies.